2006
DOI: 10.1007/s10936-005-9010-7
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Errors Predominate in Arabic Spelling Across Grades 1–9

Abstract: Most of the spelling error analysis has been conducted in Latin orthographies and rarely conducted in other orthographies like Arabic. Two hundred and eighty-eight students in grades 1-9 participated in the study. They were presented nine lists of words to test their spelling skills. Their spelling errors were analyzed by error categories. The most frequent errors were phonological. The results did not indicate any significant differences in the percentages of phonological errors across grades one to nine.Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 36 publications
7
41
2
1
Order By: Relevance
“…Significance differences were found between dyslexic children and the control group, differences that show low phonological abilities among dyslexic Arabic-speaking children. In the study by Abu-Rabia and Taha, (2006) on the Arabic language, it was also found that phonology is closely related to reading and spelling errors among native Arabic-speaking children from the first to the sixth grade (Abu-Rabia & Taha, 2006). Similar results were also obtained by the study of Abu-Rabia, Share and Mansour (2003).…”
Section: Introductionsupporting
confidence: 70%
“…Significance differences were found between dyslexic children and the control group, differences that show low phonological abilities among dyslexic Arabic-speaking children. In the study by Abu-Rabia and Taha, (2006) on the Arabic language, it was also found that phonology is closely related to reading and spelling errors among native Arabic-speaking children from the first to the sixth grade (Abu-Rabia & Taha, 2006). Similar results were also obtained by the study of Abu-Rabia, Share and Mansour (2003).…”
Section: Introductionsupporting
confidence: 70%
“…Spelling difficulties are regarded as a significant predictor of reading disability while other difficulties like emotional, socio-economical and sensory difficulties are excluded (Jimȇnez et al 2003;Fletcher and Denton 2003;Lyon et al 2002). Accordingly, a spelling test from Abu-Rabia and Taha (2006) was administered in all grades, i.e. in the 2nd (α = 0.88), 4th (α = 0.94), and 6th grade (α = 0.82).…”
Section: Participantsmentioning
confidence: 99%
“…The second type of errors was visually based, which means replacing letters that look similar. Another study was conducted by Abu-Rabia and Taha (2006) to analyse spelling data from students in Grades 1 through 9. The most interesting result of this study was that phonological spelling errors (e.g., substitution errors) were most common in all grades.…”
Section: Arabic Languagementioning
confidence: 99%
“…Spelling is now seen as one of the best ways of investigating what an individual knows about words and about the process of learning those words (Abu-Rabia & Taha, 2006). Most elementary schools in the Arab world teach spelling as an isolated subject from the other language arts, because memorisation is thought to be the explanation of its mastery.…”
Section: Significance Of the Studymentioning
confidence: 99%